CdS‐Nanoparticles‐Decorated Perpendicular Hybrid of MoS2 and N‐Doped Graphene Nanosheets for Omnidirectional Enhancement of Photocatalytic Hydrogen Evolution. Issue 15 (6th July 2016) - Zhang, Shuqu; Wang, Longlu; Zeng, Yunxiong; Xu, Yuzi; Tang, Yanhong; Luo, Shenglian; Liu, Yutang; Liu, Chengbin
Abstract: A new hierarchical nanoarchitecture with integration of multiple active materials has been developed for highly efficient hydrogen evolution reaction (HER), by decorating a perpendicular hybrid of MoS2 and N‐doped graphene nanosheets with CdS nanoparticles. The unique architecture promoted light trapping and absorption for highly efficient light harvesting and photocarrier generation, and offered an unblocked electron transport pathway for rapid charge separation/transport to suppress charge recombination. Its high surface area and high density of active sites result in highly efficient utilization of photogenerated carriers for productive HER. Significantly, without using noble metals as co‐catalysts, the photocatalysts demonstrated rapid HER rates as high as 5.01 mmol h −1 g −1 under visible‐light irradiation, which was approximately 25 times that of pure CdS. The hydrogen production remained stable after a continued test for 30 h, showing an exceedingly high performance and superior stability. Abstract : Architecture for light harvesting : A rational design of a CdS‐nanoparticles‐decorated perpendicular hybrid of MoS2 and N‐doped graphene (NRGO) nanosheets is presented, which promotes highly efficient and stable photocatalytic hydrogen evolution.